Two new species of Clubiona Latreille (Araneae: Clubionidae) from China - He, Jingchao; Liu, Xiaolei; Zhang, Feng (Zootaxa, 2016)
Clubiona Latreille, 1804, comprising approximately 78% of all Clubionidae species described so far, is the largest genus in the family. Of the 476 Clubiona species worldwide, 113 have been reported from China (World Spider Catalog 2016, Li & Lin 2016). However, the diversity of this genus in China is still insufficiently known and several new species have been described in the last few years (Wu & Zhang 2014a; Wu & Zhang 2014b; Dankittipakul & Singtripop 2014; Wang, Wu & Zhang 2015; Wu, Zheng & Zhang 2015). Among several species groups proposed to accommodate the species of the genus (Mikhailov 1995), the Corticalis group is one of the most well known in China, computing 19 species described so far for that country (Wang, Wu & Zhang 2015; Wu, Zheng & Zhang 2015). While examining spiders collected in Yunnan and Hunan provinces, China, we found two new Clubiona species of the Corticalis group, which are described below.